Multiscale Modeling Strategy of 2D Covalent Organic Frameworks Confined at an Air-Water Interface - Ortega-Guerrero, Andres; Sahabudeen, Hafeesudeen; Croy, Alexander; Dianat, Arezoo; Dong, Renhao; Feng, Xinliang; Cuniberti, Gianaurelio (Giovanni) (ACS Applied Materials and Interfaces, 2021)
Two-dimensional covalent organic frameworks (2D COFs) have attracted attention as versatile active materials in many applications. Recent advances have demonstrated the synthesis of monolayer 2D COF via an air-water interface. However, the interfacial 2D polymerization mechanism has been elusive. In this work, we have used a multiscale modeling strategy to study dimethylmethylene-bridged triphenylamine building blocks confined at the air-water interface to form a 2D COF via Schiff-base reaction. A synergy between the computational investigations and experiments allowed the synthesis of a 2D-COF with one of the linkers considered. Our simulations complement the experimental characterization and show the preference of the building blocks to be at the interface with a favorable orientation for the polymerization. The air-water interface is shown to be a key factor to stabilize a flat conformation when a dimer molecule is considered. The structural and electronic properties of the monolayer COFs based on the two monomers are calculated and show a semiconducting nature with direct bandgaps. Our strategy provides a first step toward the in silico polymerization of 2D COFs at air-water interfaces capturing the initial steps of the synthesis up to the prediction of electronic properties of the 2D material.
CRIS-Team Scopus Importer:2022-04-14
Keywords: azine linkage; covalent organic frameworks; DFT(B); Langmuir-Blodgett; MD; Schiff base reactions